Quadriceps atrophy: to what extent does it exist in patellofemoral pain syndrome? - Callaghan, M J; Oldham, J A (British journal of sports medicine, 2004)
Background: Quadriceps atrophy is a commonly cited accompaniment to patellofemoral pain syndrome (PFPS), yet there is little valid, objective evidence for its existence. Objective: To investigate atrophy and weakness of the quadriceps femoris muscle group in patients with PFPS using measures of cross-sectional area and peak extension torque. Methods: A total of 57 patients with insidious onset of PFPS and 10 healthy control subjects had ultrasound scanning of the quadriceps femoris. The scans were analysed using computerised planimetry to estimate the cross-sectional area of the quadriceps femoris. Lower limb peak torque was also measured using a Biodex dynamometer. Results: The mean of % differences revealed a 3.38% (95% confidence interval (CI) 1.3 to 5.45) difference in cross-sectional area (CSA) between the affected and unaffected limb in PFPS patients and a 1.31% (95% CI 0.06 to 2.55) difference in the dominant and non-dominant limb of the control group; the between-groups difference was not significant (p = 0.409). There was a 18.4% (95% CI 13 to 23.8) difference between the affected and unaffected limb in peak torque in PFPS patients and a 7.6% (95% CI 3.2 to 12) difference between the dominant and non-dominant limb in the control group; the between-groups difference was significant (p = 0.002). Conclusions: The mean of % differences of 3.38% quadriceps atrophy between limbs was considerably less than the only other study using ultrasound scanning on the quadriceps in PFPS and was not significant between the groups. There were greater and more significant between-group differences in lower limb peak torque indicating that muscle strength may not be related to muscle size. These results help to re-appraise of the amount of quadriceps atrophy in PFPS.